Community Self-Help
X, 163 p.
Keywords: This book explores the dynamics of community self help in local neighbourhoods. It shows how widespread it is, and argues that it should be considered as the third major sector of social and economic organization (alongside the state and market). Danny Burns, Colin C. Williams and Jan Windebank examine community self-help as a springboard into the mainstream, a complement to it, and an alternative. Finally, the book opens out a vision of social organization with self-help and mutual aid at its heart.